Ecos do oco da fome: como pesquisar e produzir saúde mental nas ruínas de um tempo? - Coutinho, Chenya Valença (2022)
In times of COVID- 19 pandemic, this research takes hunger as an analyzer of brazilian reformist movements and the democratic state of law itself in its intersections with the field of mental health. Taking the Psychiatric Reform (PR) as a civilizing process of social-subjective transmutation, the research evokes the "strong" meaning of reformist movements to address a collective mental health. In this sense, through the qualitative method and field research, the experience of feeling/living hungry, its visible and invisible effects as a health-disease problem, is presented. It rehearses an ethical policy of narractivity through the articulation of socio-economic data extracted from the base of the Ministry of Health, the Municipal Health Department of Aracaju-Sergipe and the stories brought by workers/es and users of mental health services. Thus, we hear a snoring that signals that capitalist relations (classist, racialized, gendered) are producers and managers of psychic suffering. So, this dissertation proposes to look in the eye of hunger and discuss about the revitalization of the ways of making politics, of producing health and subjectivity. It seeks, then, to present and suggest health practices that start to put at the center of the therapeutic projects and life projects construction, analysis of social structures that naturalize markers such as gender, race/ethnicity and class, to, from there, propose new modes of reception and care in mental health.